2018
DOI: 10.13189/aeb.2018.060506
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Relationship between Research and Development (R&D) and Economic Development in EU

Abstract: This paper explores the relation between R&D and economic growth using data from the EU-28 countries for the period 2001-2014. We consider panel data econometric techniques and control variables commonly used in the literature are analyzed together with a number of other variables to which existing studies often give little attention. Our results suggest that R&D expenditure and the patents (European Patent Office-EPO) have a positive and significant effect on economic growth for all countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Grossman and Helpman stressed that improvements in technology are the best option to overcome the limits of economic growth [49]. Athina et al analyzed 14 years (2000Athina et al analyzed 14 years ( -2014 of data from the European Union on R&D and economic growth, and they concluded that private R&D spending, public R&D expenditure, total R&D spending, and the number of researchers and patents positively affected the per capita GDP of the countries [17]. While in developing countries an increase of 1% in R&D expenditure introduces a 0.3-0.4% increase in economic growth, a rise of 1% in R&D spending in developed countries leads to a 1% increase in economic growth [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grossman and Helpman stressed that improvements in technology are the best option to overcome the limits of economic growth [49]. Athina et al analyzed 14 years (2000Athina et al analyzed 14 years ( -2014 of data from the European Union on R&D and economic growth, and they concluded that private R&D spending, public R&D expenditure, total R&D spending, and the number of researchers and patents positively affected the per capita GDP of the countries [17]. While in developing countries an increase of 1% in R&D expenditure introduces a 0.3-0.4% increase in economic growth, a rise of 1% in R&D spending in developed countries leads to a 1% increase in economic growth [17].…”
Section: Discussionmentioning
confidence: 99%
“…Innovation is one of the key success factors in a knowledge economy, and it is R&D that determines innovation [16]. R&D plays a significant role in the outcome and impact of business innovation, and R&D investment within a given country is one of the most powerful markers for ascertaining the level of innovation within that country [17]. Romer highlighted that investing in R&D increases the likelihood of developing high-level technologies, resulting in higher national income and greater economic growth [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 : December 2020 : pp. 5-33 used to address the relationship between R&D and growth within certain groups, such as G7 (Wälde & Woitek, 2004) or European Union (EU) countries (Athina, Athanasios, Panagiotis, Zacharias, & Dimitrios, 2018). Comparative analysis of innovation policies in 28 OECD countries shows that the pattern of R&D expenditures that influence growth differs from country to country.…”
Section: Literature Reviewmentioning
confidence: 99%